2003
DOI: 10.1890/1051-0761(2003)013[0279:abtrha]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Bt TRANSGENE REDUCES HERBIVORY AND ENHANCES FECUNDITY IN WILD SUNFLOWERS

Abstract: Abstract. Gene flow from transgenic crops can introduce novel traits into related species, but the ecological importance of this process is unknown. Here, we report the first empirical evidence that wild plants can benefit from a bacterial transgene under uncaged, natural conditions. Cultivated sunflower (Helianthus annuus) is known to hybridize frequently with wild sunflower (H. annuus) in the western and midwestern United States. We studied a crop-developed Bacillus thuringiensis (Bt) transgene, cry1Ac, in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
255
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(273 citation statements)
references
References 24 publications
17
255
1
Order By: Relevance
“…Most studies of the fitness of herbivore-or pathogen-resistant transgenes in crop-wild plant hybrids (and their backcross progeny) have tended to examine direct trade-offs in pairwise comparisons (e.g., with and without the target herbivore/pathogen) that lack the full host-natural enemy-community complex. Typically, these studies have found that seed production of hybrids carrying resistance to herbivores or pathogens increases in the presence of their target herbivores or pathogens (41)(42)(43)(44). However, upon escape into natural populations, resistance transgenes face a complex suite of direct and indirect costs.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of the fitness of herbivore-or pathogen-resistant transgenes in crop-wild plant hybrids (and their backcross progeny) have tended to examine direct trade-offs in pairwise comparisons (e.g., with and without the target herbivore/pathogen) that lack the full host-natural enemy-community complex. Typically, these studies have found that seed production of hybrids carrying resistance to herbivores or pathogens increases in the presence of their target herbivores or pathogens (41)(42)(43)(44). However, upon escape into natural populations, resistance transgenes face a complex suite of direct and indirect costs.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenes are typically inherited as dominant traits that result from strong, constitutive gene expression, with the potential to have major effects on plant fitness (e.g., Snow et al, 2003). The evaluation of biosafety risks must consider both the probability of gene flow and its potential consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The most direct method for evaluating the consequences of gene flow is to quantify the fitness effects of a transgene on hybrids between a transgenic cultivar and a wild or weedy relative under field conditions. For example, Snow et al (2003) found that a Bacillus thuringiensis (Bt) gene conferring resistance to lepidopteran herbivores increased the fecundity of hybrids between a sunflower cultivar and wild sunflower. In contrast, Burke and Rieseberg (2003) found that an oxalate oxidase transgene for white mold resistance did not confer a fecundity advantage to crop-wild hybrids in sunflower.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to oilseed production, sunflowers have become increasingly popular in recent years as a confectionery (snack food) and an ornamental crop. Apart from this commercial importance, the sunflowers have also recently moved to the center of the ecological and evolutionary stage (Burke and Rieseberg 2003;Rieseberg et al 2003;Snow et al 2003;Lexer et al 2004) alongside more well-studied organisms such as fruit flies (Drosophila spp. ), Darwin's finches (Geospiza spp.…”
Section: Introductionmentioning
confidence: 99%